ANALISIS DEBIT BANJIR PADA DAERAH ALIRAN SUNGAI UNTUK DESAIN DAN EVALUASI KAPASITAS TAMPUNG BANGUNAN AIR - -, Riman (Universitas Widyagama Malang, 2012)
Prediction of flood discharge of a river Basin is a major input for the planning and evaluation capacities of waterworks. This estimate should be the appropriate method that can produce more accurate flood predictions. Several methods have been developed by scientists, such as the analysis of rainfall intensity, frequency distribution and hidrograph unit, but the data difficult to obtain sufficient observations. Due to lack of data flow and the rain of data, the method chosen hidrograph unit as an alternative to estimate the flood discharge. Although the method has been developed hidrograph unit, not necessarily appropriate for use, because of differences in the characteristics, conditions and rainfall patterns. Based on this, needs to be reviewed and rainfall intensity analysis unit to produce hidrograf by comparing several methods. Based on the analysis of the results obtained, the comparison with the HSS Nakayasu and there is a difference HSS Gama I, intensity of Mononobe, HSS Nakayasu Q= 922,804 m3/dt, HSS Gama I Q= 595,286 m3/dt, so the difference 327,518 m3/dt (35,48%), and intensity of PSA 007, HSS Nakayasu, Q= 396,223 m3/dt, HSS Gama I Q= 413,125 m3/dt, so the difference = 16,902 m3/dt (5%). Key Words: Discharge, Flood, Design, Evaluation, Capacity.